Monetary policy adjustments in Mexico during COVID-19: Fear of floating and macroeconomic volatility - Jesús Eduardo López-Mares; Juan Manuel Ocegueda Hernández; Rogelio Varela-Llamas (Economies, 2025)
The aim of this paper is to investigate how the central bank of Mexico - a prototypical emerging market economy (EME) - adjusted its reaction coefficients according to an estimated Taylor-type rule in response to the COVID-19 pandemic and the posterior surge in inflation. To do so, we estimate a small open economy model and employ Bayesian methods with a rolling window strategy. Our findings suggest that, during and after the COVID-19 crisis, the central bank slightly reduced its response to inflation and significantly decreased the reaction to the output gap. Further, the exchange rate response increased, pointing to a higher fear of floating. Additionally, a counterfactual experiment shows that these policy adjustments effectively dampened the macroeconomic volatility during the pandemic. We attribute these changes to the lower sensitivity of inflation to the output gap and the amplification of external shocks. However, we argue that these adjustments, particularly the heightened fear of floating, are temporary measures designed to anchor inflation expectations.
Keywords: 330; monetary policy rules; macroeconomic volatility; rolling windows; Bayesian estimation; small open economy